14q12q13.2 microdeletion syndrome: Clinical characterization of a new patient, review of the literature, and further evidence of a candidate region for CNS anomalies. Issue 7 (16th May 2020) - Ponzi, Emanuela; Gentile, Mattia; Agolini, Emanuele; Matera, Emilia; Palumbi, Roberto; Buonadonna, Antonia Lucia; Peschechera, Antonia; Gabellone, Alessandra; Antonucci, Maria Fatima; Margari, Lucia
Abstract: Background: Chromosome 14q11‐q22 deletion syndrome (OMIM 613457) is a rare contiguous gene syndrome. Two regions of overlap (RO) of the 14q12q21.1 deletion have been identified: a proximal region (RO1), including FOXG 1(*164874), NKX2‐1 (*600635), and PAX9 (*167416) and a distal region (RO2), including NKX2‐1 and PAX9 . We report a 6‐year‐old boy with mild dysmorphic facial features, global developmental delay, and hypoplasia of the corpus callosum. Methods and Results: Array‐CGH analysis revealed a 14q12q13.2 microdeletion. We compared the phenotype of our patient with previously published cases in order to establish a genotype–phenotype correlation. Conclusion: The study hypothesizes the presence of a new RO, not including the previously reported candidate genes, and attempt to define the associated molecular and psychomotor/neurobehavioral phenotype. This region encompasses the distal breakpoint of RO1 and the proximal breakpoint of RO2, and seems to be associated with intellectual disability (ID), hypotonia, epilepsy, and corpus callosum abnormalities. Although more cases are needed, we speculated on SNX6 (*606098) and BAZ1A (*605680) as potential candidate genes associated with the corpus callosum abnormalities. Abstract : We report a 6‐year‐old boy with mild dysmorphic facial features, global developmental delay, and hypoplasia of the corpus callosum and 14q12q13.2 microdeletion. In order to establish a genotype‐phenotype correlation we compared the phenotype of our patient with previously published cases, hypothesize the presence of a new RO and attempt to define the associated molecular and psychomotor/neurobehavioral phenotype.